Physicians' Self-Reported Knowledge and Behaviors Related to Prescribing Opioids for Chronic Pain and Diagnosing Opioid Use Disorder, DocStyles, 2020 - Kathleen R. Ragan-Burnett, MSPH; C. Robinette Curtis, MD; Kristine M. Schmit, MD; Christina A. Mikosz, MD; Lyna Z. Schieber, MD; Gery P. Guy, Jr, PhD; Tamara M. Haegerich, PhD (Elsevier, 2024)
Introduction: In 2016, the Centers for Disease Control and Prevention released the Guideline for Prescribing Opioids for Chronic Pain (2016 Centers for Disease Control and Prevention Guideline) to improve opioid prescribing while minimizing associated risks. This analysis sought to understand guideline-concordant knowledge and self-reported practices among primary care physicians. Methods: Data from Spring DocStyles 2020, a cross-sectional, web-based survey of practicing U.S. physicians, were analyzed in 2022 and 2023. Demographic, knowledge, and practice characteristics of primary care physicians overall (N=1,007) and among specific subsets-(1) primary care physicians who provided care for patients with chronic pain (n=600), (2) primary care physicians who did not provide care for patients with chronic pain (n=337), and (3) primary care physicians who reported not obtaining or seeking a buprenorphine waiver (n=624)-were examined. Results: A majority of physicians (72.6%) were unable to select a series of options consistent with diagnostic criteria for opioid use disorder; of those physicians, almost half (47.9%) reported treating at least 1 patient with medications for opioid use disorder. A minority of physicians (17.5%) reported having a buprenorphine prescribing waiver. Among physicians who prescribed opioids for chronic pain (88.5%), 54.4% concurrently prescribed benzodiazepines. About one third (33.5%) reported not taking patients with chronic pain. Conclusions: There were critical practice gaps among primary care physicians related to 2016 Centers for Disease Control and Prevention Guideline topics. Increasing knowledge of the Centers for Disease Control and Prevention's opioid prescribing recommendations can benefit physician practice, patient outcomes, and public health strategies in addressing the opioid overdose crisis and implementing safer and more effective pain care.